Study of RHO zeolite with different cations for CO2/CO separation in pressure swing adsorption - Dan Liang; Yunfeng Hu; Qiang Bao; Jian Zhang; Penglai Sun; Jiawei Feng; Ming Xu; Hongsheng Zhang (Micro & Nano Letters, 2021)
Abstract A series of cation‐exchanged RHO zeolites, including H‐RHO, Li‐RHO, Na‐RHO, K‐RHO, Cs‐RHO, Cd‐RHO and Pb‐RHO, were prepared, and the samples were characterised by X‐ray diffraction, scanning electron microscopy, energy dispersive X‐ray spectroscopy, thermogravimetric analysis, inductive coupled plasma emission spectrometer and N2‐BET. The CO2 and CO adsorption behaviours of the samples were measured at 298 K and 0–10 bar. The Langmuir equation was used to fit adsorption isotherms to compare the separation effect of these RHO zeolites. The results show that extra‐framework cations can effectively adjust the pore size of RHO. Not only it depends on the size of the cation radius, but other factors also play an important role, such as the position of the cation. Besides, compared with CHA structure, RHO structure has better CO2/CO separation performance. In all researched cationic forms of RHO, Li‐RHO, Cd‐RHO and Pb‐RHO have excellent CO2/CO separation effects. Among them, the pore size of Cd‐RHO is significantly reduced, thereby restricting the entry of CO more effectively, ultimately leading to greater shape selectivity. Cd‐RHO not only has the highest CO2 saturated adsorption capacity and CO2 working capacity but also has relatively excellent CO2/CO selectivity, resulting in the sorbent selection parameter (S) is also the largest.